#### Answer

The answer is $1$.

#### Work Step by Step

We insert $x = -1$ in $\frac{3}{2 - x^3}$:
$\frac{3}{2 - x^3} = \frac{3}{2 - (-1)^3} = \frac{3}{2 - ((-1) \cdot (-1) \cdot(-1) ) } = \frac{3}{2 - (-1)} = \frac{3}{2 +1 } = \frac{3}{3} = 1$.

Published by
Wiley

ISBN 10:
1118583191

ISBN 13:
978-1-11858-319-7

The answer is $1$.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.